Falling rates of hospitalization and mortality from abdominal aortic aneurysms in Australia - Norman, P.; Spilsbury, Katrina; Semmens, James (Mosby Inc., 2011)
Background: Studies of the population trends for abdominal aortic aneurysms (AAAs) in the period 1970 to 2000 all indicated that the incidence of AAAs was increasing. It is not known whether this increase has continued. We hypothesized that the incidence of AAAs has begun to fall in Australia. Methods: Age-standardized national trends in mortality from AAAs were estimated for the period 1999 to 2006, and hospital separations (deaths or discharges) for AAAs were estimated for the period 1999 to 2008. Poisson regression models were constructed to estimate the relative change over time. Results: The age-standardized mortality rate from AAAs fell by an average of 6.0% (95% confidence interval [CI], 4.7-7.3) per annum in men and 2.9% (95% CI, 1.0-4.7) in women. After adjusting for age, hospital separations for men decreased by an average of 2.3% (95% CI, 1.4-2.7) per annum for nonruptured AAAs, and 5.9% (95% CI, 5.0-6.6) for ruptured AAAs and for women decreased by an average of 2.2% (95% CI, 1.4-3.0) per annum for nonruptured AAAs, and 5.1% (95% CI, 3.7-6.5) for ruptured AAAs. Ruptured, compared with nonruptured, AAAs were proportionally more common in women compared with men. The age-specific trends in separations from hospital were all downward apart from nonruptured AAAs in individuals aged 80 years and over. Conclusions: The rates of separation from hospital and mortality for AAAs in Australia have fallen since 1999. This suggests a true fall in incidence of AAAs. Although the reasons for this are unknown, it has implications for policy decisions about screening.